ANALISIS KELENTUKAN PERGELANGAN TANGAN TERHADAP PUKULAN DROPSHOT PADA ATLET BULUTANGKIS PB. UKHUWAH - Inez Fricilia Wengkau; Wahyudin Wahyudin; Abdul Rahman (Jurnal Ilara : Jurnal Hasil Penelitian, Aplikasi Teori, Analisa, Dan Pembahasan Kepustakaan tentang Keolahragaan, 2023)
This study is a correlational study that aims to determine the contribution of hand flexibility to dropshot strokes in badminton athletes PB. Ukhuwah. The independent variable in this study is flexibility and the other variable is the drop shot. The sample in this study were 10 male athletes of PB. Ukhuwah who had an average age of 12-18 years who were taken using a saturated/total population sampling technique. Furthermore, data collection for each research variable was carried out using a measuring instrument of hand flexibility using an arc ruler and a dropshot test. The data analysis technique used is descriptive test, data normality test, and hypothesis testing. The results of the categorization test showed that the average score on the flexibility test was in the hands, namely 162.50 in the sufficient category, while the average in the dropshot test was 14.20 in the category. the results of this study's hypothesis testing: correlation value r = 0.560 P = 0.093 (P > 0.05) means that there is an insignificant relationship between flexibility based on hitting the dropshot in PB badminton athletes. brotherhood While R2 = 0.313, the key is to contribute to the flexibility of the hands against the PB badminton athlete's strokes. Brotherhood of R2 = 31%, the remaining 69% is influenced by other factors